-
Notifications
You must be signed in to change notification settings - Fork 1
/
Copy pathPruebas_de_∃x∃yP(x,y)↔∃y∃xP(x,y).lean
151 lines (127 loc) · 3.11 KB
/
Pruebas_de_∃x∃yP(x,y)↔∃y∃xP(x,y).lean
1
2
3
4
5
6
7
8
9
10
11
12
13
14
15
16
17
18
19
20
21
22
23
24
25
26
27
28
29
30
31
32
33
34
35
36
37
38
39
40
41
42
43
44
45
46
47
48
49
50
51
52
53
54
55
56
57
58
59
60
61
62
63
64
65
66
67
68
69
70
71
72
73
74
75
76
77
78
79
80
81
82
83
84
85
86
87
88
89
90
91
92
93
94
95
96
97
98
99
100
101
102
103
104
105
106
107
108
109
110
111
112
113
114
115
116
117
118
119
120
121
122
123
124
125
126
127
128
129
130
131
132
133
134
135
136
137
138
139
140
141
142
143
144
145
146
147
148
149
150
151
-- Pruebas de ∃x∃yP(x,y) ↔ ∃y∃xP(x,y)
-- ==================================
import tactic
section
variable {U : Type}
variable {P : U -> U -> Prop}
-- ----------------------------------------------------
-- Ej. 1. Demostrar que
-- ∃x∃yP(x,y) → ∃y∃xP(x,y)
-- ----------------------------------------------------
-- 1ª demostración
example :
(∃ x, ∃ y, P x y) → (∃ y, ∃ x, P x y) :=
assume h1 : ∃ x, ∃ y, P x y,
exists.elim h1
( assume a (h2 : ∃ y, P a y),
exists.elim h2
( assume b (h3 : P a b),
have h4 : ∃ x, P x b, from exists.intro a h3,
show ∃ y, ∃ x, P x y, from exists.intro b h4))
-- 2ª demostración
example :
(∃ x, ∃ y, P x y) → (∃ y, ∃ x, P x y) :=
assume ⟨a, b, (h1 : P a b)⟩,
have h2 : ∃ x, P x b, from ⟨a, h1⟩,
show (∃ y, ∃ x, P x y), from ⟨b, h2⟩
-- 3ª demostración
example :
(∃ x, ∃ y, P x y) → (∃ y, ∃ x, P x y) :=
assume ⟨a, b, (h1 : P a b)⟩,
show (∃ y, ∃ x, P x y), from ⟨b, ⟨a, h1⟩⟩
-- 4ª demostración
example :
(∃ x, ∃ y, P x y) → (∃ y, ∃ x, P x y) :=
assume ⟨a, b, (h1 : P a b)⟩,
show (∃ y, ∃ x, P x y), from ⟨b, a, h1⟩
-- 5ª demostración
example :
(∃ x, ∃ y, P x y) → (∃ y, ∃ x, P x y) :=
assume ⟨a, b, (h1 : P a b)⟩,
⟨b, a, h1⟩
-- 6ª demostración
example :
(∃ x, ∃ y, P x y) → (∃ y, ∃ x, P x y) :=
λ ⟨a, b, h1⟩, ⟨b, a, h1⟩
-- 7ª demostración
example :
(∃ x y, P x y) → (∃ y x, P x y) :=
-- by library_search
exists_comm.mp
-- 8ª demostración
example :
(∃ x, ∃ y, P x y) → (∃ y, ∃ x, P x y) :=
begin
intro h1,
cases h1 with a h2,
cases h2 with b h3,
use b,
use a,
exact h3,
end
-- 9ª demostración
example :
(∃ x, ∃ y, P x y) → (∃ y, ∃ x, P x y) :=
begin
intro h1,
cases h1 with a h2,
cases h2 with b h3,
use [b, a],
exact h3,
end
-- 10ª demostración
example :
(∃ x, ∃ y, P x y) → (∃ y, ∃ x, P x y) :=
begin
intro h1,
rcases h1 with ⟨a, b, h2⟩,
use [b, a],
exact h2,
end
-- 11ª demostración
example :
(∃ x, ∃ y, P x y) → (∃ y, ∃ x, P x y) :=
begin
intro h1,
rcases h1 with ⟨a, b, h2⟩,
exact ⟨b, a, h2⟩,
end
-- 12ª demostración
example :
(∃ x, ∃ y, P x y) → (∃ y, ∃ x, P x y) :=
begin
rintro ⟨a, b, h2⟩,
exact ⟨b, a, h2⟩,
end
-- 13ª demostración
example :
(∃ x, ∃ y, P x y) → (∃ y, ∃ x, P x y) :=
-- by hint
by tauto
-- 14ª demostración
lemma aux :
(∃ x, ∃ y, P x y) → (∃ y, ∃ x, P x y) :=
by finish
-- ----------------------------------------------------
-- Ej. 2. Demostrar que
-- ∃x∃yP(x,y) ↔ ∃y∃xP(x,y)
-- ----------------------------------------------------
-- 1ª demostración
example :
(∃ x y, P x y) ↔ (∃ y x, P x y) :=
iff.intro aux aux
-- 2ª demostración
example :
(∃ x y, P x y) ↔ (∃ y x, P x y) :=
⟨aux, aux⟩
-- 3ª demostración
example :
(∃ x y, P x y) ↔ (∃ y x, P x y) :=
-- by library_search
exists_comm
-- 4ª demostración
example :
(∃ x y, P x y) ↔ (∃ y x, P x y) :=
-- by hint
by tauto
end